Fabrication of Mebendazole Loaded Solid Lipid Nanoparticles: Formulation, Optimization, Characterization, Stabilization, and In-Vitro Evaluation (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The research focused on the formulation, optimization, characterization stabilization and in vitro evaluation of Mebendazole loaded solid lipid nanoparticles (MEB-SLN) using response surface methodology. MEB-SLN was developed using the melt-emulsification ultrasonication method. The optimized formulation contains Compritol 888 ATO as a solid lipid and Poloxamer 407 as a surfactant. The optimized MEB-SLN was spherical, and had an average size of 230.4nm, and zeta potential of -21.9mV. The physiochemical characterization included the evaluation of surface morphology, drug entrapment, x-ray diffraction studies, and differential scanning calorimetry. In vitro drug release studies revealed that MEB-SLN would release drugs for up to 24 hrs. The formulation was found to be significantly quite stable in the refrigerator than at room temperature, as per stability tests. As a result of these findings, MEB-SLN was identified as a possible drug carrier. This provides a framework for further exploration of the developed formulation.